CNTM-02. Regulation of glioma-network integration by tumor mediated secretion of TSP-1. (12th November 2021) - Negussie, Mikias; Krishna, Saritha; Hervey-Jumper, Shawn
Abstract: Glioma exists in the complex neural circuitry of the brain, making the interface between neoplastic and healthy neurons and glia potentially damaging to long range neural networks and stimulatory to tumor growth. Thrombospondin-1 (TSP-1), an astrocyte derived neurogenic factor expressed by glia of the normal brain, has been found to be upregulated in intratumoral regions with high network functional connectivity (HFC). This modified cell signaling represents cancer cell hijacking of normal physiology with direct impact on tumor biology. There is emerging evidence that neuronal activity influences glioma proliferation and gliomas promote neuronal hyperexcitability. In humans, we have recently shown that bidirectional cellular interactions between gliomas and neurons alter cognitive circuit dynamics and ultimately patient survival. Previously, a subpopulation of human high-grade glioma cells which are enriched for tumor cells with synaptogenic potential were identified (HFC-IHDwtGBM). We plan to study the mechanisms of TSP1 signaling in three different established glioma models (1) HFC-IDHwtGBM hippocampal neuron co-culture, (2) HFC-IDHwtGBM + induced neuron organoids, (3) patient derived xenografts (PDX) for in vivo GCaMP calcium imaging. This project aims to test the hypothesis that increased TSP-1 secretion from HFC-IHDwtGBM cells plays a central role in the maintenance of an invasive and proliferative tumor phenotype when compared with LFC-IHDwtGBM PDX. We hope our study guides future work focused on preventing the infiltration of tumor cells into healthy brain tissues.